Strategies For Improving Teacher Performance Through Strengthening Organizational Culture, Transformational Leadership, Self-Efficacy, And Work Motivation: Empirical Study Using Quantitative Approach and Sitorem Analysis on Private High School Teachers in Depok City, West Java - Dewi Mutiara Indah Ayu; Isman Kadar; Widodo Sunaryo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In the world of education, teachers have a very large and important role in teaching and learning activities because teachers are educators who are directly in contact with students, so teachers are required to have good performance in order to teach students who also have good quality. One of the educational problems faced by the Indonesian nation is the quality of education at every level and education unit, especially elementary and secondary education. Various efforts have been made to improve the quality of education, including through various training and improving teacher qualifications, procuring books and teaching tools, improving facilities and infrastructure, and improving the quality of school management. The research method used in this study is quantitative through path analysis and SITOREM analysis. The results of this study are that there is a positive relationship between the independent variable and the dependent variable when viewed from the path analysis, then the relationship is a functional relationship where teacher performance (Y) is formed as a result of the functioning of organizational culture functions (X1), transformational leadership (X2), self-efficacy (X3) work motivation (X4)